Experimental models of portal hypertension - Beguiristain, Alberto; Gastambide, Carmelo; Arévalo, Ethel; Posteiro, Alvaro; Alvarez, Manuel; Bonaba, Roberto (Cirugía del Uruguay, 1978)
Two methods for producing experimental portal hypertension in dogs are analyzed: Plastic casein constrictors and Dimetilnitrosamine (D.M. N .A. ) . Positive resuits were obtained in 75 % of cases utilizing the former method and in 70 % when utilizing the Iatter. The use of constrictors is technically laborious and D.M. N.A. is highly toxical.